In vitro antitubercular screening and in silico study of germacradienolide from blainvillea latifolia - Honmore, Varsha; Kalyankar, Vidya; Natu, Arun; Khedkar, Vijay; Sarkar, Dhiman; Rojatkar, Supada (Asian Journal of Chemistry, 2021)
Bioassay-guided isolation from acetone extract of Blainvillea latifolia yielded one compound. The acetone extract, fractions and the compound 1 were investigated for antitubercular activity against Mycobacterium tuberculosis H37Ra. Compound 1 showed the activity with IC50 and MIC values at 8.9 and >100 μg/mL. However, the acetone extract of Blainvillea latifolia was inactive against two Gram negative (E. coli, P. flurescence) and two Gram-positive (S. aureus, B. subtilis) bacterial strains. Hence, it was concluded that the extract and the compound 1 are specifically active against MTB and not against bacterial strains. Molecular docking study was performed against crucial mycobacterial target MtInhA to gain an insight into the binding mode and the thermodynamic interactions governing the binding affinity of this molecule.